2008
DOI: 10.1080/09670260802172627
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity, temperature, dissolved inorganic carbon and nutrient concentration on the photosynthesis and growth ofFucus vesiculosusfrom the Baltic and Irish Seas

Abstract: Fucus vesiculosus from the northern Baltic Sea (5 psu) and from the Irish Sea (35 psu) were cultivated at different temperatures, salinities and dissolved inorganic carbon (DIC) concentrations with the addition of different nutrient concentrations. The influence of these abiotic factors was assessed by measuring photosynthesis as electron transport rate (ETR) and growth as relative growth rate (RGR ). When Baltic F. vesiculosus was cultivated at a DIC concentration similar to that of the Irish Sea, the ETR as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
2
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 40 publications
6
68
2
5
Order By: Relevance
“…We discovered that light and temperature have interactive effects on growth (and therefore should be quantified and reported), but Fortes & Lüning did not report light levels for their experiment; a direct comparison is therefore difficult and the reported differences could thus be due to different culture conditions. Furthermore, Nygaard & Dring (2008) reported optimum growth for F. vesiculosus comparable to this study at longterm temperatures down to 15-20°C. Overall these differences in optimum temperatures suggest the presence of regional ecotypes that are adapted to prevailing environmental conditions.…”
Section: Discussionsupporting
confidence: 58%
“…We discovered that light and temperature have interactive effects on growth (and therefore should be quantified and reported), but Fortes & Lüning did not report light levels for their experiment; a direct comparison is therefore difficult and the reported differences could thus be due to different culture conditions. Furthermore, Nygaard & Dring (2008) reported optimum growth for F. vesiculosus comparable to this study at longterm temperatures down to 15-20°C. Overall these differences in optimum temperatures suggest the presence of regional ecotypes that are adapted to prevailing environmental conditions.…”
Section: Discussionsupporting
confidence: 58%
“…On the other hand, C. tamariscifolia growing in RS may be subjected to different cycles of desiccation and rewetting, increasing atmospheric CO 2 uptake and nutrient incorporation; the inorganic carbon uptake in C. tamariscifolia growing in rockpools depend mainly on the amount of dissolved HCO 3 -and carbon concentration mechanisms (CCMs) through carbonic anhydrase (CA), with the consequent energy cost (Falkowski 1997). It has been reported that intertidal algae under moderate desiccation conditions have higher nitrogen and phosphate uptakes (Lobban andHarrison 1994, Nygard andDring 2008), photosynthetic rates Brown 1982, Mercado et al 1998). The carbon incorporation under emersion is higher than that under submerged conditions due to the direct uptake of CO 2 (Flores-Moya et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…High CO 2 and/or dissolved inorganic carbon (DIC) conditions stimulate growth and photosynthesis of different non-calcifying seaweeds (Gordillo et al 2001, Nygård and Dring 2008, Wu et al 2008, Olischläger et al 2012, Saderne 2012, Koch et al 2013). In addition to the effect of enhanced CO 2 on growth and photosynthesis of seaweeds, reproduction may be impacted by the DIC concentration in seawater.…”
Section: Reproduction Under Ocean Warming and Acidificationmentioning
confidence: 99%